2004
DOI: 10.1139/z04-141
|View full text |Cite
|
Sign up to set email alerts
|

A swimming activity assay shows that the thermal tolerance ofDaphnia magnais influenced by temperature acclimation

Abstract: Daphnia magna Straus, 1820 is a widespread zooplanktic organism enduring considerable changes in oxygen concentration and temperature within its natural habitat. The thermal tolerance window of D. magna was analyzed using the animals' swimming activity as a test parameter in a photometrical assay. Acclimation to different temperatures (10, 20, 30 °C) resulted in a shift of the thermal optimum corresponding to acclimation conditions. Acclimation to warm temperatures also increased the upper thermal tolerance li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Following the 2 h thermal incubation, specimens were immediately placed at 15 1C and held for 12 h before survival was assessed. Specimens not reacting to gentle agitation for 15 s were considered dead (Zeis et al, 2004). Thermal tolerance of each culture was calculated as the temperature when 50% mortality occurred (LT 50 ), as calculated from the linear model of arcsin squareroot transformed percent survival expressed in radians regressed to incubation temperature (Stillman and Somero, 2000).…”
Section: Acute Thermal Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Following the 2 h thermal incubation, specimens were immediately placed at 15 1C and held for 12 h before survival was assessed. Specimens not reacting to gentle agitation for 15 s were considered dead (Zeis et al, 2004). Thermal tolerance of each culture was calculated as the temperature when 50% mortality occurred (LT 50 ), as calculated from the linear model of arcsin squareroot transformed percent survival expressed in radians regressed to incubation temperature (Stillman and Somero, 2000).…”
Section: Acute Thermal Tolerancementioning
confidence: 99%
“…All tests of salinity tolerance were conducted at 15 1C. Following the 2 h salinity incubation, specimens were transferred to COMBO water salinity 0 and held at 15 1C for 12 h. Specimens not reacting to gentle agitation for 15 s were considered dead (Zeis et al, 2004). Salinity tolerance of each culture was calculated as the salinity when 50% mortality occurred (LC 50 ), calculated in the same manner as for LT 50 above.…”
Section: Acute Salinity Tolerancementioning
confidence: 99%
“…However, we observed that individuals at temperatures approaching CT min had greatly reduced swimming activity (they mostly rested on the bottom of the glasses and were easy to pick up during transfer, in contrast with Diaphanosoma at higher T ) and would in nature almost certainly fall victim to predation. A decrease of swimming activity as temperatures approach the thermal limits has been reported also in other cladocerans and has been explained by a mismatch between the energy supplied by the animal's aerobic metabolism at low temperatures and the energy demand of swimming activity (Zeis et al ).…”
Section: Discussionmentioning
confidence: 79%
“…Variation in TPCs due to acclimation, hardening, rate of temperature change, or duration of exposure can complicate predictions based on TPCs constructed in constant thermal environments (Sinclair et al ). Significant interactions between acclimation temperature, the duration of exposure to thermal extremes and the temperature of subsequent recovery have all been shown to affect the survival of D. magna (Zeis et al ). In this study, adult individuals of both Diaphanosoma species were able to survive for a time at temperatures at which they were not able to produce viable offspring.…”
Section: Discussionmentioning
confidence: 99%
“…While Daphnia can tolerate lower DO concentrations when acclimated over time (Zeis et al 2004), the experimental animals were not acclimated (temperature or DO) prior to the experiments, be cause our objective was to evaluate DO tolerance of D. mendotae in response to abrupt shifts in temperature and DO concentration that they experience during their DVM. Bottles were immediately sealed to minimize changes in DO concentration and placed in incubators to maintain constant temperatures (10 or 25°C) with an 11 h light:13 h dark photoperiod.…”
Section: Laboratory Experiments 1: Temperature and Do Effects On Survimentioning
confidence: 99%